Low-Bit Hybrid RIS Enhanced Beamforming Design With Imperfect CSI - Guo, Yeyong; Zhang, Peichang; Peng, Yi; Ye, Junjie; Huang, Lei; Chen, Zhen (IEEE International Conference on Signal and Image Processing Applications (Online), 2024)
Reconfigurable Intelligent Surface (RIS) is considered as a promising tool for improving wireless communication due to its various advantages. However, owing to the effect of "multiplicative fading" and practical hardware limitations, it is very limited for passive RIS to enhance the wireless communication quality of service under the assumption of imperfect channel state information (CSI). In this paper, we investigate a low-bit hybrid RIS-aided multi-user communication system, where a subset of RIS elements are fully connected to power amplifiers (PAs). Firstly, we utilize alternating optimization (AO) and fractional programming (FP) algorithm to solve the continuous phase shift optimization problem. Furthermore, we develop a discrete phase shift optimization method based on genetic algorithm (GA) to maximize the sum rate (SR) of all users at low precision quantization. Simulation results show that the hybrid RIS scheme is better than the passive RIS schemes. Furthermore, compared with the conventional low precision quantization optimization method, the proposed GA algorithm can effectively improve the system performance.